The species of Uroleucon (Hemiptera: Aphididae) living on Adesmia (Fabaceae) in Argentina, with the description of a new species - Nafría, Juan Manuel Nieto; Von Dohlen, Carol D.; Moreno-González, Víctor; Ortego, Jaime; Durante, M. Pilar Mier (Zootaxa, 2019)
Uroleucon Mordvilko is the largest genus in the Macrosiphini (Hemiptera, Aphididae) and most of its species live on species of Asteraceae. Uroleucon nahuelhuapense Nieto Nafría & von Dohlen sp. n. is described from apterous viviparous females collected on Adesmia boronioides (Fabaceae) in a locality of Neuquén province (Argentina). The morphological characters and the sequence of the tRNAleu-COII mitochondrial locus support the inclusion of the new species in the genus Uroleucon. Apterous viviparous females of Uroleucon adesmiae Mier Durante & Ortego collected in two Argentinean localities have also been studied and ranges of several quantitative features have been modified. The identification key for the Uroleucon species known in South America by Nieto Nafría et al. (2007) has been modified to include the new species.